Carabid (Coleoptera) Community Changes Following Prescribed Burning and the Potential Use of Carabids as Indicators Species to Evaluate the Effects of Fire Management in Mediterranean Regions - Nunes,Luisa (2006)
This study investigates the effects of prescribed burning on ground beetle (Coleoptera: Carabidae) communities in two different habitats, a pine forest stand in Northern Portugal and a shrubland in a central region that were fire treated in spring of 1998. These two ecosystems were considerably different floristically as well as structurally. Pitfall trapping was performed for two years in the pine stand and three years in the shrubland. Species of dryer open habitats dominated after fire in the shrubland site while the pine stand habitat showed a more or less constant carabid community structure for all treatments. Some Carabid taxa such as species/subspecies like Chrysocarabus lateralis, Petrophilus brevipennis sousai, Macrothorax rugosus celtiberus and Steropus globosus ebenus may be considered as indicators for fire managed areas in Mediterranean ecosystems.